Comparative efficacy and safety of reperfusion therapy with fibrinolytic agents in patients with ST-segment elevation myocardial infarction: a systematic review and network meta-analysis. Issue 10096 (19th August 2017) - Jinatongthai, Peerawat; Kongwatcharapong, Junporn; Foo, Chee Yoong; Phrommintikul, Arintaya; Nathisuwan, Surakit; Thakkinstian, Ammarin; Reid, Christopher M; Chaiyakunapruk, Nathorn
Summary: Background: Fibrinolytic therapy offers an alternative to mechanical reperfusion for ST-segment elevation myocardial infarction (STEMI) in settings where health-care resources are scarce. Comprehensive evidence comparing different agents is still unavailable. In this study, we examined the effects of various fibrinolytic drugs on clinical outcomes. Methods: We did a network meta-analysis based on a systematic review of randomised controlled trials comparing fibrinolytic drugs in patients with STEMI. Several databases were searched from inception up to Feb 28, 2017. We included only randomised controlled trials that compared fibrinolytic agents as a reperfusion therapy in adult patients with STEMI, whether given alone or in combination with adjunctive antithrombotic therapy, against other fibrinolytic agents, a placebo, or no treatment. Only trials investigating agents with an approved indication of reperfusion therapy in STEMI (streptokinase, tenecteplase, alteplase, and reteplase) were included. The primary efficacy outcome was all-cause mortality within 30–35 days and the primary safety outcome was major bleeding. This study is registered with PROSPERO (CRD42016042131). Findings: A total of 40 eligible studies involving 128 071 patients treated with 12 different fibrinolytic regimens were assessed. Compared with accelerated infusion of alteplase with parenteral anticoagulants as background therapy, streptokinase and non-accelerated infusion of alteplase were significantly associated with an increased risk of all-cause mortality (risk ratio [RR] 1·14 [95% CI 1·05–1·24] for streptokinase plus parenteral anticoagulants; RR 1·26 [1·10–1·45] for non-accelerated alteplase plus parenteral anticoagulants). No significant difference in mortality risk was recorded between accelerated infusion of alteplase, tenecteplase, and reteplase with parenteral anticoagulants as background therapy. For major bleeding, a tenecteplase-based regimen tended to be associated with lower risk of bleeding compared with other regimens (RR 0·79 [95% CI 0·63–1·00]). The addition of glycoprotein IIb or IIIa inhibitors to fibrinolytic therapy increased the risk of major bleeding by 1·27–8·82-times compared with accelerated infusion alteplase plus parenteral anticoagulants (RR 1·47 [95% CI 1·10–1·98] for tenecteplase plus parenteral anticoagulants plus glycoprotein inhibitors; RR 1·88 [1·24–2·86] for reteplase plus parenteral anticoagulants plus glycoprotein inhibitors). Interpretation: Significant differences exist among various fibrinolytic regimens as reperfusion therapy in STEMI and alteplase (accelerated infusion), tenecteplase, and reteplase should be considered over streptokinase and non-accelerated infusion of alteplase. The addition of glycoprotein IIb or IIIa inhibitors to fibrinolytic therapy should be discouraged. Funding: None.